Analisis Loyalitas Pelanggan PT. Pegadaian ditinjau dari Kualitas Layanan, Citra Perusahaan dan Kepuasan - May Fitri Jesicha Sari; Sri Wahyuni Megah; Supriyono Supriyono (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This research aims to understand and explain the influence of the variable service quality, corporate image, and customer satisfaction on customer loyalty. This type of research is quantitative approach. The sample in this research as much as 90 respondents who Rahn pawn customer at PT. Pegadaian (Persero) Syariah Cabang Pasar Legi - Jombang by using accidental sampling technique. Data collection methods used in this research is to disseminate the questionnaire. The analysis of the data used multiple regression. The research results showed that the variables of service quality, corporate image, and customer satisfaction has a positive and significant effect on customer loyalty.